Faculty reactions to some aspects of vocational education in Marikina School of Arts and Trades - Tajon, Angeles (Fres) 1930- (s.n.], 1973)
This study surveyed the reactions of the faculty of MSAT towards selected aspects of vocational education. The faculty's reactions relative to the curriculum, school plant, methods of instruction, ancillary services and techniques and practices in supervision were determined. Furthermore, the implications of this study to the administration was also derived.